Factors associated with dropout in a group weight‐loss programme: a longitudinal investigation. (14th February 2014) - Yackobovitch‐Gavan, M.; Steinberg, D. M.; Endevelt, R.; Benyamini, Y.
Abstract: Background: Attrition is a major limitation of most weight management intervention programmes. The present study aimed to conduct an extensive investigation of personal, sociodemographic and treatment‐related factors associated with attrition at different stages of a 10‐week group weight‐loss programme. Methods: The present study is part of a longitudinal, clinical intervention study comparing three conditions in a 10‐week group programme: Control, Behavioural Intentions and Implementation Intentions. The study included 587 participants with a mean (SD) age of 46 (11) years (range 18–78 years) and a mean (SD) body mass index (BMI) of 31.9 (5.5) kg m –2, with 90% being female. To characterise dropout in each week separately, as well as overall dropout (dropout until week 9, the median time of dropout), we tested several logistic regression models, including multiple imputations to cope with missing data. Results: The results of the different dropout models consistently showed that a smaller reduction in BMI in the first 2 weeks of the programme was the strongest predictor of dropout. Dropout in the tenth and last week differed from the earlier weeks both in the relatively high dropout rate (56% of total dropout) and in that, in contrast to earlier weeks, the week 10 model included the reduction in BMI during the last 2 weeks before dropout but did not include the reduction in BMI at the initiation of the intervention. Conclusions: Weight‐loss in the beginning of the programme is a crucial independent determinant of dropout in each week except the last one. This finding is important because it suggests a simple assessment for a major dropout risk factor in adult weight‐loss intervention programmes.